The 6-min walk test: responses in healthy Canadians aged 45 to 85 years - Hill, Kylie; Wickerson, L.; Woon, L.; Abady, A.; Overend, T.; Goldstein, R.; Brooks, D. (Canadian Scientific Publishers, 2011)
We sought to describe responses to the 6-min walk test (6MWT) in healthy Canadian adults in order to facilitate interpretation of its results in patient populations. Seventy-seven healthy Canadians aged 45 to 85 years (65 ± 11 years, 40 females) completed this study. During a single visit, three 6MWTs were undertaken. The main outcome measure was 6-min walk distance (6MWD). Age, gender, height, and weight were recorded. In 61 (79%) participants, cardiorespiratory variables were collected during the third 6MWT using a calibrated portable gas analysis system. The 6MWD increased between the first and second test (615 ± 96 to 639 ± 98 m; p < 0.001) with no further improvement on the third test (638 ± 99 m; p = 0.945). The best 6MWD from the first 2 tests was 640 ± 99 m (range 416 to 880 m). A greater 6MWD was achieved by males compared with females (672 ± 94 vs. 611 ± 93 m; p = 0.005). The following equation accounted for 49% of the variance in 6MWD: 6MWD = 970.7 + (–5.5 × age) + (56.3 × gender), where females = 0, males = 1. The 6MWT elicited large cardiorespiratory responses with minimal symptoms. The rate of oxygen uptake measured at test-end was associated with the 6MWD (r = 0.802; p < 0.001). These data allow the 6MWD achieved in Canadian adults to be expressed as a percentage of the predicted value and provide researchers and clinicians with values for the expected cardiorespiratory responses in a healthy adult population for the purpose of comparison with patient populations.